Relationship Between Frequency Of Tension Type Headache (TTH) In Epilepsy With Cognitive Function - Diah Patlika; Herlina Suryawati; M.I. Widiastuti; Endang Kustiowati; Hexanto Muhartomo; Arinta Puspita Wati (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background : Epilepsy is a chronic disease that increases the risk of interictal headaches, one of which is tension type headache (TTH). TTH in epilepsy is triggered by recurrent neurogenic inflammation and central sensitization leading to pericranial tenderness. Recurrent neurogenic inflammation can affect cognitive function. The frequency of TTH in epilepsy is thought to be related to cognitive function score.Objective : Analyzing the relationship between the category of TTH frequency, onset of epilepsy, seizure frequency, age and education with cognitive score.Methods : Our study is an analytic observational study with a cross sectional design that took place from April to September 2021. The subjects of the study were epilepsy patients suffering from TTH at Dr. Kariadi Hospital, Semarang who met the inclusion and exclusion criteria. Patients’s data was obtained by filling out a questionnaire form. Assessment of the category of TTH frequency used ICHD-3 beta 2013 criteria. Assessment of cognitive function used the MoCA-Ina score. Data was analyze with Spearman correlation test, the results were significant if the p value <0.05.Results : Forty one epilepsy patients consist of 14 infrequent episodic TTH, 14 frequent episodic TTH and 13 chronic TTH. There was significant relationship between the MoCA-Ina score and the TTH frequency category (r=0,362; p=0,02), and education level (r=0,493; p=0,001). There was a weak relationship between the MoCA-Ina score and the onset of epilepsy or seizure frequency, while there was no relationship with age.Conclusion : There was a moderate relationship between the TTH frequency in epilepsy with cognitive function. Keywords : epilepsy, tension type headache (TTH), Montreal Cognitive Assesment -  Indonesian version (MoCA-Ina)